Characterizing and Modeling the Mechanical Properties of the Cement Mortar Modified with Fly Ash for Various Water-to-Cement Ratios and Curing Times - Warzer Qadir; Kawan Ghafor; Ahmed Mohammed (Advances in Civil Engineering)
Despite many research studies on the effect of the fly ash content (FA) on the mechanical behavior of the cement mortar, there has not been an extensive study investigating the effect of FA, curing time (t), and water-to-cement ratio (w/c) on the compressive (σc), tensile (σt), and flexural (σf) strengths of cement mortar. Therefore, this study investigates the subject which could be beneficial for the building and construction field. In this study, more than 1000 data on the mechanical properties of the cement mortar modified with different percentages of fly ash varying from 5% to 75% (by dry weight of the cement) were collected from the literature. The statistical analysis and modeling were performed on the collected data. The w/c of the cement mortar ranged from 0.20% to 0.80%, and the compressive, split tensile, and flexural strengths of cement mortar modified with fly ash and cured up to 90 days ranged from 15 MPa to 88 MPa, 0.4 MPa to 5 MPa, and 1 MPa to 10 MPa, respectively. The Vipulanandan model was also used and compared with the Hoek–Brown model to correlate the mechanical properties of cement mortar modified with fly ash. The results of this study showed that there is a good relationship between the compressive strength (σc) and w/c, curing time, and fly ash content. The compressive, split tensile, and flexural strengths of cement mortar quantified well as a function of w/c, fly ash content, and curing time using a nonlinear relationship.